2012
DOI: 10.1371/journal.pone.0041616
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signatures of Cardiac Defects in Down Syndrome Lymphoblastoid Cell Lines Suggest Altered Ciliome and Hedgehog Pathways

Abstract: Forty percent of people with Down syndrome exhibit heart defects, most often an atrioventricular septal defect (AVSD) and less frequently a ventricular septal defect (VSD) or atrial septal defect (ASD). Lymphoblastoid cell lines (LCLs) were established from lymphocytes of individuals with trisomy 21, the chromosomal abnormality causing Down syndrome. Gene expression profiles generated from DNA microarrays of LCLs from individuals without heart defects (CHD−; n = 22) were compared with those of LCLs from patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 61 publications
3
30
0
Order By: Relevance
“…In comparison with a previous study based on the same microarray profiling, 10) a different DEG screening method and criteria were utilized in our study. The limma package 18) used in the present study is the most widely used software in DEG screening, and the criteria of P < 0.05 and |log 2 FC| > 0.5 are strict enough to ensure the significance of DEGs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In comparison with a previous study based on the same microarray profiling, 10) a different DEG screening method and criteria were utilized in our study. The limma package 18) used in the present study is the most widely used software in DEG screening, and the criteria of P < 0.05 and |log 2 FC| > 0.5 are strict enough to ensure the significance of DEGs.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray data: Gene expression profiling of GSE34457 10) was downloaded from the Gene Expression Omnibus (GEO) database (http://www.ncbi.nlm.nih.gov/geo/), based on the platform of GPL6102 (Illumina human-6 v2.0 expression beadchip). A total of 22 samples from DS patients without congenital heart disease and 7 samples from DS patients with AVSD were utilized in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study of rare partial trisomy 21 cases suggested the presence of a minimal, 1.77-Mb CHD candidate region at 21q22.3, between markers D21S3 and PFKL (Korbel et al, 2009). Recent studies have also suggested the potential contribution of VEGFA (Ackerman et al, 2012), cleome and Hedgehog (Ripoll et al, 2012), and folate (Locke et al, 2010) pathways to the pathogenicity of DS-CHD. The transcription profile of DS-CHD was obtained based on the Hsa21 genes in the heart of 18-22-week-old human fetuses (Conti et al, 2007).…”
Section: Introductionmentioning
confidence: 99%